Phosphorus Fractionation Responds to Dynamic Redox Conditions in a Humid Tropical Forest Soil. Issue 9 (22nd September 2018) - Lin, Yang; Bhattacharyya, Amrita; Campbell, Ashley N.; Nico, Peter S.; Pett‐Ridge, Jennifer; Silver, Whendee L.
Abstract: Phosphorus (P) is a key limiting nutrient in highly weathered soils of humid tropical forests. A large proportion of P in these soils is bound to redox‐sensitive iron (Fe) minerals; however, little is known about how Fe redox interactions affect soil P cycling. In an incubation experiment, we changed bulk soil redox regimes by varying headspace conditions (air versus N2 gas) and examined the responses of soil P and Fe species to two fluctuating treatments (4‐ or 8‐day oxic followed by 4‐day anoxic) and two static redox treatments (oxic and anoxic). A static anoxic headspace increased NaOH‐extractable inorganic P and ammonium oxalate‐extractable total P (AO‐Pt ) by 10% and 38%, respectively, relative to a static oxic headspace. Persistent anoxia also increased NaHCO3 ‐extractable total P (NaHCO3 ‐Pt ) toward the end of the experiment. Effects of redox fluctuation were more complex and dependent on temporal scales. Ammonium oxalate‐extractable Fe and Pt concentrations responded to redox fluctuation early in the experiment, but not thereafter, suggesting a depletion of reductant over time. Immediately following a switch from an oxic to anoxic headspace, concentrations of AO‐Pt, AO‐Fe, and HCl‐extractable Fe(II) increased (within 30 min) but fell back to initial levels by 180 min. Surprisingly, the labile P pool (NaHCO3 ‐Pt ) decreased immediately after reduction events, potentially due to resorption and microbial uptake. Overall, our data demonstrate that P fractions can respond rapidly to changes in soil redox conditions, and in environments where redox oscillation is common, roots and microbes may benefit from these rapid P dynamics. Key Points: Shortly after redox switches, some soil P fractions showed tight coupling with iron speciation Amorphous Fe and P fractions became less sensitive to redox fluctuation over time Static anoxic conditions increased P extractability and enhanced iron reduction